2016
DOI: 10.1111/myc.12529
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole: an emerging therapeutic option for invasive rhino‐orbito‐cerebral mucormycosis

Abstract: Posaconazole has significant activity against the Mucormycetes. However, data are limited on the clinical efficacy of posaconazole for treating rhino-orbito-cerebral mucormycosis (ROCM). The aim of this study is to assess the efficacy and safety of posaconazole in patients with ROCM. We included 12 consecutive adult patients admitted with ROCM and treated with posaconazole between January 2010 and February 2015. The main outcome of the study was the overall success rate (i.e. either complete or partial respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 18 publications
2
33
0
1
Order By: Relevance
“…In contrast, Dai et al (9) and Saegeman et al (7) have reported the mean ages of 58.8 and 60 years, respectively. Although mucormycosis has been reported to be more common in males compared with females in most of the published series (1,3,4,7,9,16,20), in the present study, females (68%) were more affected than males (32%), which is in accordance with reports by Komur et al (21) from Turkey Rhinocerebral mucormycosis is the most common clinical form of this infection (4,6,17,21,23), which is in agreement with our results. In our study, similar to a report by Roden et al (17) from the United States of America, rhinocerebral mucormycosis with or without orbital involvement was the major manifestation in diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, Dai et al (9) and Saegeman et al (7) have reported the mean ages of 58.8 and 60 years, respectively. Although mucormycosis has been reported to be more common in males compared with females in most of the published series (1,3,4,7,9,16,20), in the present study, females (68%) were more affected than males (32%), which is in accordance with reports by Komur et al (21) from Turkey Rhinocerebral mucormycosis is the most common clinical form of this infection (4,6,17,21,23), which is in agreement with our results. In our study, similar to a report by Roden et al (17) from the United States of America, rhinocerebral mucormycosis with or without orbital involvement was the major manifestation in diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are inconsistent with the results of Zaki et al (3) from Egypt, which demonstrated pulmonary mucormycosis as the major manifestation in diabetic patients. In this report, diabetes mellitus (68%) was the common risk factor for mucormycosis, which supports other studies (3,4,20,24), as expected in tropical and developing countries (3,6). However, in some other studies, hematologic malignancy has been reported as the most common predisposing factor for mucormycosis (21,25).…”
Section: Discussionsupporting
confidence: 90%
“…147 Infection of sinuses is more common in patients with poorly controlled diabetes. 112,183,184 Progression into the orbit 185 or intracranially, via direct extension or angioinvasion 107,122 may occur rapidly (within days). Brain involvement is associated with a high mortality.…”
Section: Rhino-orbital-cerebral Involvementmentioning
confidence: 99%
“…190,191 POSA is considered salvage therapy, but complete responses were achieved with POSA in 8 of 12 cases in a recent series of ROCM. 183…”
Section: Rhino-orbital-cerebral Involvementmentioning
confidence: 99%
“…The most common classic form of this mycosis is its rhinocerebral form . Mucormycosis usually affects diabetic patients, recipients of transplants or stem cells, patients with blood dyscrasias, patients with neutropenia, patients taking deferoxamine, those taking corticosteroids, patients affected by severe burns, intravenous drug users, patients with cancers, subjects receiving traumas due to falls, who are affected by dust, and those with HIV . However, in some patients no predisposing factors are detected …”
Section: Introductionmentioning
confidence: 99%